A review of the genus Hoplasoma (Coleoptera: Chrysomelidae: Galerucinae) from Sulawesi, Indonesia, with the description of H. bosi sp. nov. - Bezděk, Jan (Zootaxa, 2008)
The species of the genus Hoplasoma Jacoby, 1884, family Chrysomelidae, from Sulawesi are reviewed. One species new to science, H. bosi Bezděk, sp. nov., is described. Hoplasoma celebensis ab. butonensis Weise, 1922 is treated as an infrasubspecific unavailable name conspecific with H. celebense Jacoby, 1886. The lectotypes are designated for H. apicale Jacoby, 1884, H. celebense Jacoby, 1886 and H. rostripenne Allard, 1888. The drawings of male abdomina and male genitalia are presented for all species. Identification key for species from Sulawesi is given. The gender of the generic name Hoplasoma is explained and fixed as neutrum.